MAXIMIZATION OF DNA DAMAGE TO MGMT(+) EGFR(+) GBM CELLS USING OPTIMAL COMBINATION OF TEMOZOLOMIDE-ANTI EGFR MONOCLONAL ANTIBODY NIMOTUZUMAB - Inggas, Made Agus Mahendra; Wahjoepramono, Eka J.; Maliawan, Sri; Islam, Andi Asadul (BALI MEDICAL JOURNAL, 2015)
Background: Glioblastoma multiforme (GBM) is the most aggressive primary brain tumor in adultswith dismal prognosis due to the unavailability of an effective therapy. Up to now, there had been no definitive studies published on EGFR inhibition therapy as a chemosensitizer for GBM therapy using Temozolomide (TMZ). This study aims to reveal the most effective method and timing to administer TMZ anti EGFR targeted therapy which causes maximal DNA damage on GBM cells. Methods: Various regimens of anti EGFR monoclonal antibody Nimotuzumab (NMZ) was administered in different combinations with TMZ, performed on U87MG MGMT(+) EGFR(+) cells. The effectiveness of the combinations were evaluated by measuring yH2AX levels which reflects the degree of DNA damage. One-way Anova and LSD tests were performed to determine the effects of each treatment with p<0.05. Results and discussion: the mean SD of yH2AX of each treatment was: 11,90±1,25 for the control group; 29.33±1.91 for NMZ alone; 28.13±1.58 for TMZ alone; 41.53±3.51 for concurrent use; 35.67 ±2.65 for NMZ after 24 hours TMZ; 31.87±2.94 for NMZ after 48 hours TMZ; 39.57±4.2 for TMZ after 24 hours NMZ; and 35.93 ±3.56 for TMZ after 48 hours NMZ. The administration of TMZ concurrent with or after 24 hours NMZ gives the highest amount of DNA damage to GBM cells. Conclusion: The administration of Nimotuzumab targeted therapy up to 24 hours before Temozolomide chemotherapy has been proven to be effective in maximizing the amount of DNA damage done to GBM cells in vitro.
Keywords: Glioblastoma; multiforme; Temozolomide; anti EGFR; Monoclonal